IMMU-05. COMBINATIONAL CAR T-CELL AND EPIGENETIC MODIFIER THERAPY TO TARGET POSTERIOR FOSSA TUMORS. (23rd April 2019) - Donovan, Laura; Bielamowicz, Kevin; Joseph, Sujith; Delaidelli, Alberto; Sorenson, Poul; Ahmed, Nabil; Taylor, Michael
Abstract: Posterior Fossa tumours (PFTs) are the leading cause of cancer-related death in children, with medulloblastoma and ependymoma (EP) the most prevalent. PFTs continue to be treated with non-specific toxic therapies, with survivors suffering life threatening morbidities. PFTs are known to have distinct molecular sub-types; here we focus on two PFTs—Group 3 medulloblastoma and Posterior Fossa A (PFA) EP—which have the worst outcomes and are restricted to children. Actionable and recurrent mutations are rare in these PFTs; we recently confirmed the presence of three Chimeric Antigen Receptor (CAR) target antigens, EPHA2, HER2 and IL13R2, for use as mono-CARs, TRI CARs, and in combinational therapy with the epigenetic modifier Azacitidine. Pre-clinical trials showed CAR delivery via the lateral ventricle gave the most significant survival benefit (P<0.0005), therefore all downstream therapies were delivered intrathecally. Group 3 medulloblastoma: trials using one treatment round (1R) of EPHA2 CARs showed significant tumor regression versus T cell (P<0.005) and no-treatment (NT) (P<0.0005). The use of 2Rs of EPHA2 CARs to target tumor recurrence resulted in significant tumor regression (P<0.0005) versus NT, with progression-free survival (PFS) observed at >500 days post therapy. Combination therapy of 1R EPHA2 CARs with Azacitidine gave significant tumor regression versus EPHA2 CARs alone (P<0.0005). PFA EP: trials using HER2 (P<0.05) or TRI CARs (P<0.005) showed significant tumor regression versus T cell controls, and most subjects showed increased PFS. CARs with combinational Azacitidine therapy resulted in PFS in every PFA EP subject. We show that intrathecal CAR therapy combined with Azacitidine significantly increases survival rates in Group 3 medulloblastoma and PFS for PFA EP. Results from this project have created a paradigm shift in the treatment of PFTs, with the initiation of a clinical trial for HER2+ PFA EP treatment, and the capacity for future clinical trials for Group 3 medulloblastoma.